2020
DOI: 10.1186/s12879-020-4798-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal antigenemia is associated with meningitis or death in HIV-infected adults with CD4 100–200 cells/mm3

Abstract: Background: Cryptococcal antigen (CrAg) screening with fluconazole prophylaxis has been shown to prevent cryptococcal meningitis and mortality for people living with HIV (PLWH) with CD4 < 100 cells/mm 3 . While cryptococcal meningitis occurs in individuals with CD4 100-200 cells/mm 3 , there is limited evidence that CrAg screening predicts cryptococcal meningitis or mortality among this group with moderate immunosuppression. Current IDSA and WHO clinical guidelines recommend restricting CrAg screening to PLWH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…In this review, over 80% of the studies included reported a CD4 count of less than 50 cells/mm 3 at baseline. Unlike most studies that suggest that the occurrence of CM is common in those with CD4 count less than 200, our study found an even lower CD4 count as a common finding ( 23 , 56 ). This could explain why the majority of our studies had a mortality percentage greater than 30% which was comparable to 44% (short-term mortality) reported by Tenforde et al ( 31 ) and 36.7% by Majumder et al ( 57 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this review, over 80% of the studies included reported a CD4 count of less than 50 cells/mm 3 at baseline. Unlike most studies that suggest that the occurrence of CM is common in those with CD4 count less than 200, our study found an even lower CD4 count as a common finding ( 23 , 56 ). This could explain why the majority of our studies had a mortality percentage greater than 30% which was comparable to 44% (short-term mortality) reported by Tenforde et al ( 31 ) and 36.7% by Majumder et al ( 57 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Patients who presented with either a low Glasgow coma scale, altered behavior, or simply altered mental status died or had a longer hospital admission ( 19 22 ). Furthermore, a CD4 count between 100 and 200 cells/mm 3 predisposes one with CM to worse symptoms and clinical outcomes ( 23 ). Anemia is a hematological finding that has been reported as a significant contributor to 2 and 10-week mortality if present in the moderate to severe forms at baseline ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions occur in HIV-infected patients whose CD4 count has collapsed (<100 cells/mm 3 ). Although serum screening for cryptococcal antigens is reserved for an HIV-positive person having a CD4 T cell count of less than 100 cells/mm 3 according to current WHO guidelines [ 25 ], a recent study highlights that a positive cryptococcal antigens result was strongly associated with an increased risk of cryptococcal meningitis or death [ 26 ]. Those authors suggest that raising the threshold for cryptococcal antigens screening to 200 cells/mm 3 could help reduce morbidity and mortality in HIV-infected patients in cryptococcus-endemic regions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing a targeted screening of HIV patients with low body mass index, CD4 count < 100 cells, having headaches; and treatment for asymptomatic cryptococcal disease should be considered among inpatients infected by HIV in DRC. Additional data is needed to better define the epidemiology of cryptococcal antigenemia and its predictors in DRC in order to optimize the prevention, diagnosis, and treatment strategies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 8 ]. However, CrAg positivity appears to predict cryptococcal meningitis and death even at a cutoff of <200 cells/mm 3 among ART-naïve PWH [ 9 ]. The World Health Organization (WHO) recommends CrAg screening among newly diagnosed PWH with a CD4 count <100 cells/mm 3 , and conditionally among those with a CD4 count of 100–200 cells/mm 3 [ 10 ].…”
mentioning
confidence: 99%